Assessment of Antidiabetic Potential and Phytochemical Profiling of Viscum album, a Traditional Antidiabetic Plant. (4th August 2022) - Ullah, Manzoor; Mehmood, Sultan; Khan, Rehmat Ali; Ali, Maroof; Fozia, Fozia; Waqas, Muhammad; Ullah, Riaz; Alotaibi, Amal; Sultan, Mujeeb A.
Abstract : The traditional antidiabetic plant Viscum album ( V. album ) was collected from the oak plant in the wild at Maidan, Khyber District, of Pakistan, for assessment of its antidiabetic potential and phytochemical profile. Lowering of blood glucose level, antioxidant effect, lipids proﬁle, liver function marker enzymes, and kidney function markers were evaluated in extract and glibenclamide treated groups, in normal as well as in diabetic control groups. An elevated level of blood glucose level, lipids (Cholesterol, TG, LDL), liver function marker enzymes (ALT, AST, ALP), and kidney function markers (bilirubin, creatinine, urea) were observed in alloxan-induced diabetic rats; however, a HDL level was decreased. Administration of V. album hydroalcoholic extract for 28 days renovated significantly (p < 0.05 ) all the above biochemical parameters. The antioxidant enzymes SOD, CAT, and GPX were also considerably restored. In vitro, antioxidant assay indicated that the extract of 2, 000  µ g/mL scavenges free radicals of DPPH 68.4%, ABTS 69.5%, and H2 O2 50.6%. The extracts revealed the presence of saponins, flavonoids, alkaloids, terpene, tannins, phenols, protein, amino acids, sterols, and glycosides. The extract has shown phenolic contents 421 ± 4.8 mg GAE/100 g d. w and flavonoids content 127 ± 1.4 mg equiv. Rut/100 g d. w. The findings of this research recommend V. album could be a potent source of natural antidiabetic constituents.